Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5603/ait.a2018.0023
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin in liver dysfunction — Dr Jekyll or Mr Hyde?

Abstract: Serum procalcitonin (PCT) is a sensitive biomarker used for the diagnosis of infection and sepsis. PCT has also some toxic effects. It is not a proinflammatory stimulus, but may augment the inflammatory processes. High levels of PCT in sepsis may lead to hepatocyte necrosis and, as a result, to liver failure. The pathomechanism of the toxic effect of PCT is still unknown. The influence of liver function on PCT levels has not been studied yet. It is not sure whether the liver dysfunction affects the diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…Interestingly, signi cantly higher levels of PCT were observed in the SALD group compared to the no-SALD group (3.99 vs 28.0 ng/ml). Even though there was no correlation between PAI-1 and PCT in our study group, it has been shown in an in vitro study on a human hepatocyte model that high concentrations of procalcitonin might impair the hepatocytes function and lead to liver injury [33,34].…”
Section: Resultscontrasting
confidence: 67%
“…Interestingly, signi cantly higher levels of PCT were observed in the SALD group compared to the no-SALD group (3.99 vs 28.0 ng/ml). Even though there was no correlation between PAI-1 and PCT in our study group, it has been shown in an in vitro study on a human hepatocyte model that high concentrations of procalcitonin might impair the hepatocytes function and lead to liver injury [33,34].…”
Section: Resultscontrasting
confidence: 67%
“…PCT has been questioned as an index of bacterial infection in patients with liver diseases as several studies have demonstrated elevated PCT levels in the absence of bacterial infection in such patients[ 18 , 27 , 28 ]. We previously showed that PCT was not the best parameter of infection in cirrhotic patients following the onset of sepsis[ 29 ].…”
Section: Discussionmentioning
confidence: 99%